Pharmacotherapy vs surgery as initial therapy for patients with moderate‐to‐severe benign prostate hyperplasia: a cost‐effectiveness analysis. (11th September 2018) - Erman, Aysegul; Masucci, Lisa; Krahn, Murray D.; Elterman, Dean S.
Abstract : Objective: To evaluate the cost‐effectiveness of using a surgery, such as transurethral resection of the prostate (TURP) or photoselective vaporisation of the prostate using greenlight laser (GL‐PVP), as initial treatment for men with moderate‐to‐severe benign prostate hyperplasia (BPH) compared to the standard practice of using pharmacotherapy as initial treatment followed by surgery if symptoms do not resolve. Patients and Methods: We compared a combination of eight strategies involving upfront pharmacotherapy (i.e., α‐blocker, 5α‐reductase inhibitor, or combination) followed by surgery (e.g. TURP or GL‐PVP) upon failure vs TURP or GL‐PVP as initial treatment, for a target population of men with moderate‐to‐severe BPH symptoms, with a mean age of 65 years and no contraindications for treatment. A microsimulation decision‐analytic model was developed to project the costs and quality‐adjusted life years (QALYs) of the target population over the lifetime. The model was populated and validated using published literature. Incremental cost‐effectiveness ratios (ICERs) were determined. Cost‐effectiveness was evaluated using a public payer perspective, a lifetime horizon, a discount rate of 1.5%, and a cost‐effectiveness threshold of $50 000 (Canadian dollars)/QALY. Sensitivity and probabilistic analyses were performed. Results: All options involving an upfront pharmacotherapy followed by TURP for those who fail were economically unattractive compared to strategies involving a GL‐PVP for those who fail, and compared to using either BPH surgery as initial treatment. Overall, upfront TURP was the most costly and effective option, followed closely by upfront GL‐PVP. On average, upfront TURP costs $1015 more and resulted in a small gain of 0.03 QALYs compared to upfront GL‐PVP, translating to an incremental cost per QALY gained of $29 066. Results were robust to probabilistic analysis. Conclusions: Surgery is cost‐effective as initial therapy for BPH. However, the health and economic evidence should be considered concurrently with patient preferences and risk attitudes towards different therapy options.